The Neoarchean Ophiolite in the North China Craton： Early Precambrian Plate Tectonics and Scientific Debate - Kusky, Timothy M.; Zhai, Mingguo (Journal of earth science (Wuhan, China), 2012)
Archean greenstone belts and their possible inclusion of fragments of ophiolites is an im-portant research subject, since it is correlated with the nature of early oceanic crust, and can yield in-formation on the nature of early planetary lithospheres, the origin of TTG （tonalite-trondhjemite-granodiorite） continental crust, the formation of early cratons and continents, and is related to when plate tectonics started in the Earth＇s evolutionary history. This article briefly reviews the North China craton＇s Archean ophiolite argument and proposes further studies aimed at understanding the genera- tion of greenstone belts and Archean ophiolites, and suggests some key scientific questions that remain to be answered.